Аппаратная реализация преобразования SubBytes алгоритма шифрования Rijndael (AES) - Дербунович, Леонид Викторович; Караман, Дмитрий Григорьевич (НТУ "ХПИ", 2008)
Проведено аналіз існуючих рішень апаратної реалізації підстановлюючого блоку S-Box, що є основою перетворення SuBytes алгоритму шифрування Rijndael. Виконано синтез, моделювання та верифікацію динамічних і функціональних характеристик найбільш поширених варіантів на основі їхніх описів мовою VHDL.

Analysis of existing solutions for substitution module S-Box hardware implementations which is the basic part of SubBytes transformation in Rijndael encryption algorithm is provided. Synthesis, modeing and dynamic and functional characteristics verification for the most popular options based on appropriate VHDL source codes are performed.
Keywords: подстановочный блок; аппаратная схема; криптографические средства; аффинное преобразование; универсальный блок; байт